Boston Infill Schools - Stull, Don.; Heder, Lajos; Boston Public Schools, MA. Educational Planning Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Concepts and recommendations are presented regarding a proposed system of dispersed classroom clusters or 'infill schools'. These small independent urban schools would be housed in prefabricated structures developed for infill housing in Boston. The infill unit uses pre-designed building components and can be constructed in a few weeks. The infill housing units are described and their proposed use as educational facilities discussed. Diagrammatic representations illustrate the interrelationship of infill schools and community resources. The development of a pilot infill school is proposed. (FS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Facilities Design; Facility Expansion; Facility Requirements; School Construction; Building Systems; Prefabrication; School Buildings; School Planning; Urban Schools